Valore educativo del lavoro: uno sguardo alla prospettiva della sinistra pedagogica italiana durante la metà del Novecento - Silvia Annamaria Scandurra (Firenze University Press, 2019)
During the twentieth century, pedagogical research focused its attention on ways to integrate practical knowledge into formal learning paths. The spread of the scientific organization of work, the birth of the proletariat and mass education, made clear, in the first decades of the twentieth century, the complexity of the relationship between mechanization and education. it then became necessary to imagine an integrated conception of the educational process in which the formative moment and the application moment come together to create an organic link between education and work understood as "a single block of problems". The reflections of Lucio Lombardo Radice and Dina Bertoni Jovine, will allow us to recognize the emergency, still present today, to imagine a renewed school where theoretical activity and practical activity are indistinguishable and education is not understood as "a generic preparation for life, nor for the formation of professional skills, but embraces the whole human being penetrating into the depths of his personality and developing it universally".